Doctors' knowledge of the law on withholding and withdrawing life‐sustaining medical treatment. Issue 4 (11th August 2014) - White, Ben; Willmott, Lindy; Cartwright, Colleen; Parker, Malcolm H; Williams, Gail
Abstract: Objectives: To examine doctors' level of knowledge of the law on withholding and withdrawing life‐sustaining treatment from adults who lack decision‐making capacity, and factors associated with a higher level of knowledge. Design, setting and participants: Postal survey of all specialists in emergency medicine, geriatric medicine, intensive care, medical oncology, palliative medicine, renal medicine and respiratory medicine on the AMPCo Direct database in New South Wales, Victoria and Queensland. Survey initially posted to participants on 18 July 2012 and closed on 31 January 2013. Main outcome measures: Medical specialists' levels of knowledge about the law, based on their responses to two survey questions. Results: Overall response rate was 32%. For the seven statements contained in the two questions about the law, the mean knowledge score was 3.26 out of 7. State and specialty were the strongest predictors of legal knowledge. Conclusions: Among doctors who practise in the end‐of‐life field, there are some significant knowledge gaps about the law on withholding and withdrawing life‐sustaining treatment from adults who lack decision‐making capacity. Significant consequences for both patients and doctors can flow from a failure to comply with the law. Steps should be taken to improve doctors' legal knowledge in this area and to harmonise the law across Australia.